Protein and energy levels in creep feed rations for suckling pigs - Costa, Valdomiro; Fialho, Elias T.; Gomes, Paulo Cezar; Ferreira, Aloisio Soares (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out at the Centro Nacional de Pesquisa de Suínos e Aves, in Concórdia, SC, Brazil, aiming to compare the effects of different crude protein levels and digestible energy in creep fed rations, on the performance of 384 Landrace suckling piglets, from 14 to 35 days old. Six treatments and eight replications were used in 3 x 2 factorial. Levels of 22, 19 and 16% of crude protein were combined with 3.400 and 3,580 kcal/kg of digestible energy, respectively. At three days old, the number of piglets in each litter was equalized to eight, and creeps fed rations were freely offered after piglets were ten days old. After weaning, 30 litters were reared to 70 days old under stand conditions of feeding. The difference among the treatment was not statistically significant (P >0.05) at the 5% level of significance. Average daily gains were: 0.214, 0.207, 0.207, 0.216, 0198, 0.206 kg, and feed intake: 0.467, 0.493, 0.469, 0.484, 0.438 and 0.448 kg for the six treatments, corresponding to rations with: 22% of crude protein (3.400 g and 3.580 kcal/kg); 19% of crude protein (3.400 g and 3.580 kcal/kg); and 16%of crude protein (3.400g and 3.580 kcal/kg), respectively. The tested rations fed to weaning piglets did not statistically influence the performance of the pigs after weaning.